Psychological aspects of training young handball players - Abdueva Sitorabonu Savriddin qizi (Research Parks Publishers, 2021)
The article discusses the problem of psychological aspects of training young handball players. The relevance and importance of the process studied in the theory and practice of physical education and sports was grounded. The results of a survey on the peculiarities of the psychological training of young handball players are presented. The results of the experiments are analyzed, psychological and pedagogical interpretation of the results is given